Numerical Simulation Of Mudflow Interaction With Sabo-Dam By Using Two Dimensional Depth-Averaged Model - Yeoh, Chun Xian (Universiti Sains Malaysia, 2022)
Mudflow is a geological phenomenon characterized by fast-moving landslides that are threatening to life and property by destroying everything on their path without any warning. Mudflow has a higher concentration of fine particle sediments in fluid, in which, the sediment grains consist of significant portion of fine particles, silts, sands and clay. Sabo-dam is one of the selected mitigation methods to overcome mudflow in Malaysia. This research is motivated by the need to mitigate the effects of mudflow disasters which are normally triggered due to intense rainfall level, uncontrolled deforestation and land use of highland. A two-dimensional depth-averaged model (DA-CIP-2D) with Constrained Interpolation Profile (CIP) scheme was developed to simulate mudflow using the topography data of Batu Hampar, Gunung Jerai, Kedah. The DA-CIP-2D model was verified with partial dam-break problem against analytical solution and then the rheological model was validated against experimental data from literature study. The validated DA-CIP-2D was used to simulate mudflow and its interaction with Sabo-dam. Results demonstrated the ability of the model to simulate mudflow with the presence of Sabo-dam. The effect of Sabo-dam height in mitigating the peak velocity and peak flow depth, and their arrival time was well demonstrated by using the DA-CIP-2D model. With a 6.0 m Sabo structure, the peak velocity, peak flow depth and final runout length can be reduced by as much as 21.2%, 6.5% and 5.5% respectively. Increasing the height Sabo structure could further mitigate the peak velocity and peak flow depth, but at the expense of increasing the chances of flooding at the upstream part of the Sabo structure.